The Cambridge handbook of personality disorders - Lejuez, Carl W. 1971-; Gratz, Kim L. ca. 20./21. Jh (Cambridge Handbooks in Psychology, 2020)
This Handbook provides both breadth and depth regarding current approaches to the understanding, assessment, and treatment of personality disorders. The five parts of the book address etiology; models; individual disorders and clusters; assessment; and treatment. A comprehensive picture of personality pathology is supplied that acknowledges the contributions and missteps of the past, identifies the crucial questions of the present, and sets a course for the future. It also follows the changes the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) has triggered in the field of personality disorders. The editors take a unique approach where all chapters include two commentaries by experts in the field, as well as an author rejoinder. This approach engages multiple perspectives and an exchange of ideas. It is the ideal resource for researchers and treatment providers at all career stages